Identifying and prioritizing the obstacles to the establishment of human resource accounting systems of Bank Mellat in Hormozgan province - Niloofar Davoodian, Mehdi Desineh, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The purpose of this study is to identify and prioritize the obstacles to the establishment of Bank Mellat human resource accounting systems in Hormozgan province of Iran. This research is based on the applied purpose, in terms of nature and method of descriptive-correlational research and in terms of cross-sectional time. The statistical population of this research is the staff and accountants of Bank Mellat in Hormozgan province of Iran during 2021, whose number is about 371 people. In this study, Cochran's formula was used to determine the sample size and 189 people were selected as the sample size using a simple random sampling method. A questionnaire was used to collect the information required for the research, the reliability of which was confirmed by Cronbach's alpha test. To provide a proper interpretation of the data, first the statistical population was studied using descriptive analysis. After a descriptive study of the statistical population of the research, inferential methods (correlation test and multiple regression) and using SPSS software version 24 were used for statistical analysis. The results showed that there is a significant relationship between identifying and prioritizing barriers to human resource accounting systems.